Studies on Dielectric and Ferroelectric Behaviour of L-Alanine Single Crystal - Loganayaki, M.; Murugakoothan, P. (Asian Journal of Chemistry, 2011)
Single crystals of L-alanine have been grown by slow evaporation solution technique. Single crystal XRD analysis confirms the orthorhombic structure of the grown crystals. The FTIR spectral analysis has been carried out by KBr pellet technique in order to identify the functional groups present in grown crystals. The dielectric measurements on these crystals are carried out with a fully automated impedance analyzer. The dielectric constants and dielectric loss at different temperatures and frequencies of the applied field are measured and their behaviour has been analyzed. P-E hysteresis loop has been investigated at 50 Hz.